Assessing the effect of physical differences in the articulation of consonants and vowels on audiovisual temporal perception - Vatakis, Argiro; Maragos, Petros; Rodomagoulakis, Isidoros; Spence, Charles (Frontiers in Integrative Neuroscience, 2012)
We investigated how the physical differences associated with the articulation of speech affect the temporal aspects of audiovisual speech perception. Video clips of consonants and vowels uttered by three different speakers were presented. The video clips were analysed using an auditory-visual signal saliency model in order to compare signal saliency and behavioural data. Participants made temporal order judgments (TOJs) regarding which speech-stream (auditory or visual) had been presented first. The sensitivity of participants’ TOJs and the point of subjective simultaneity (PSS) were analyzed as a function of the place, manner of articulation, and voicing for consonants, and the height/backness of the tongue and lip-roundedness for vowels. We expected that in the case of the place of articulation and roundedness, where the visual-speech signal is more salient, temporal perception of speech would be modulated by the visual-speech signal. No such effect was expected for the manner of articulation or height. The results demonstrate that for place and manner of articulation, participants’ temporal percept was affected (although not always significantly) by highly-salient speech-signals with the visual-signals requiring smaller visual-leads at the PSS. This was not the case when height was evaluated. These findings suggest that in the case of audiovisual speech perception, a highly salient visual-speech signal may lead to higher probabilities regarding the identity of the auditory-signal that modulate the temporal window of multisensory integration of the speech-stream.